Appraisal of Non-Cardiovascular Safety for Sodium–Glucose Co-Transporter 2 Inhibitors: A Systematic Review and Meta-Analysis of Placebo-Controlled Randomized Clinical Trials - Shi, Fang-Hong; Li, Hao; Shen, Long; Zhang, Zhen; Jiang, Yi-Hong; Hu, Yao-Min; Liu, Xiao-Yan; Gu, Zhi-Chun; Ma, Jing; Lin, Hou-Wen (Frontiers in Pharmacology, 2019)
Background The cardiovascular safety of sodium-glucose co-transporter 2 (SGLT2) inhibitors has been well reported, only limited data and no comparisons have been published on their non-cardiovascular safety, which was the focus of our study. Methods and findings We systematically searched MEDLINE, EMBASE, and Cochrane Library (5th Sep 2018) for RCTs that reported safety data for SGLT2 inhibitors and placebo. Relative risks (RRs) and their 95% confidence intervals (CIs) were pooled using random-effects models. 70 researches (83 studies enrolling 36958 patients in 78 publications) were identified. SGLT2 inhibitors was associated with a lower risk of serious adverse events (RR 0.90, 95% CI 0.86 to 0.94, P < 0.001), death (RR 0.78, 95% CI 0.64 to 0.94, P < 0.05), gastroenteritis (RR 0.38, 95% CI 0.20 to 0.72, P < 0.05), arthralgia (RR 0.72, 95% CI 0.54 to 0.96, P < 0.05), hypertension (RR 0.61, 95% CI 0.50 to 0.75, P < 0.001) and edema/peripheral edema (RR 0.49, 95% CI 0.33 to 0.72, P < 0.001) compared to placebo. Whereas, SGLT2 inhibitors were associated with higher risk of infections compared to placebo (RR 1.27, 95% CI 1.17 to 1.37, P < 0.001), especially for genital mycotic infection (GMI) (RR 3.71, 95% CI 3.19 to 4.32, P < 0.001). Other significant effects were observed for osmotic diuresis-related AEs (RR 2.73, 95% CI 2.20 to 3.40, P < 0.001), volume-related AEs (RR 1.26, 95% CI 1.08 to 1.46, P < 0.05), renal related AEs (RR 1.36, 95% CI 1.02 to 1.80, P < 0.05), hypoglycemia (RR 1.18, 95% CI 1.10 to 1.26, P < 0.001), increased blood ketone bodies (RR 2.00, 95% CI 1.01 to 3.97, P < 0.05). Subgroup and sensitivity analyses strengthened the robustness of primary results. Conclusion Results from RCTs confirmed lower risk of death, serious adverse events, hypertension and edema associated with type 2 diabetes mellitus (T2DM) patients treated with SGLT2 inhibitors when compared with placebo. The use of SGLT2 inhibitors were associated with higher risk of infection, osmotic diuresis, volume depletion effects, renal related AEs, and higher blood ketone bodies when compared with placebo.